2008
DOI: 10.1111/j.1556-4029.2008.00852.x
|View full text |Cite
|
Sign up to set email alerts
|

Facial Soft Tissue Depths in Craniofacial Identification (Part I): An Analytical Review of the Published Adult Data*

Abstract: With the ever increasing production of average soft tissue depth studies, data are becoming increasingly complex, less standardized, and more unwieldy. So far, no overarching review has been attempted to determine: the validity of continued data collection; the usefulness of the existing data subcategorizations; or if a synthesis is possible to produce a manageable soft tissue depth library. While a principal components analysis would provide the best foundation for such an assessment, this type of investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
241
0
32

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(283 citation statements)
references
References 62 publications
10
241
0
32
Order By: Relevance
“…As expected, STT at these landmarks was larger in the 13 year old group compared to the 10 year old group. These differences are all less than 3 mm and the practical value of such small differences have been questioned [18,[23][24][25]. In practical terms few significant differences were seen between age groups and the STT increased at only at two landmarks with age.…”
Section: Tablementioning
confidence: 97%
See 4 more Smart Citations
“…As expected, STT at these landmarks was larger in the 13 year old group compared to the 10 year old group. These differences are all less than 3 mm and the practical value of such small differences have been questioned [18,[23][24][25]. In practical terms few significant differences were seen between age groups and the STT increased at only at two landmarks with age.…”
Section: Tablementioning
confidence: 97%
“…CT and MRI values produced the lowest discrepancies [18]. Stephan and Simpson [18] have shown that even though differences in methodology render different values, these values often do not differ significantly in terms of statistical or practical application.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations